Experimental Validation of the HVAC Humming-type Noise and Vibration in Model and Vehicle System Levels - SATAR, Mohd Hafiz Abdul; MAZLAN, Ahmad Zhafran Ahmad; HAMDAN, Muhd Hidayat; ISA, Mohd Syazwan Md; PAIMAN, Muhd Abdul Rahman; GHAPAR, Mohd Zukhairi Abd (Archives of Acoustics, 2021)
The presence of noises in the vehicle cabin is an annoyance phenomenon which is significantly affected by the heating, ventilation, and air conditioning (HVAC) system. There are very limited studies reported on the specific type of noise characterisation and validation for both model and vehicle system levels. The present study developed a model of HVAC system that reflects the operation as in real vehicle, and the investigation of the HVAC components were carried out individually to determine which component contributes to the humming-type noise and vibration. The study was conducted under two conditions; idle speed of engine (850 rpm) and operating condition (850–1400 rpm). A ixed blower speed and fullface setting were applied throughout the experimental process. Three different sensors were used for the experiment, which are: accelerometer, tachometer, and microphone. From the results, the compressor and AC pipe components have contributed the most in generating the noise and vibration for both the model and vehicle systems. The findings also highlight that the humming-type noise and vibration were produced in the same operating frequency of 300–400 Hz and 100–300 Hz for idle and operating conditions, respectively, and this result was validated for both model and vehicle system levels.